2022
DOI: 10.1021/acs.jpca.2c03366
|View full text |Cite
|
Sign up to set email alerts
|

Isomer-Resolved Mobility-Mass Analysis of α-Pinene Ozonolysis Products

Abstract: Highly oxygenated organic molecules (HOMs) are important sources of atmospheric aerosols. Resolving the molecular-level formation mechanisms of these HOMs from freshly emitted hydrocarbons improves the understanding of aerosol properties and their influence on the climate. In this study, we measure the electrical mobility and mass-to-charge ratio of α-pinene oxidation products using a secondary electrospray-differential mobility analyzer-mass spectrometer (SESI-DMA-MS). The mass-mobility spectrum of the oxidat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…The broad DT distribution indicates the presence of multiple isomers of C 10 H 16 O 3 in the PSOA mixture. Previous study investigating isomers of C 10 H 16 O 3 generated in the ozonolysis of α-pinene reported the presence of up to three individual peaks for C 10 H 16 O 3 species ionized as Na + adducts . Therefore, the two small shoulder peaks on both the compact and extended sides of DT distribution may be related to isomers or conformers of pinonic acid + Na + , while the abundant peak centered at 21.66 ms most likely corresponds to pinonic acid.…”
Section: Resultsmentioning
confidence: 89%
See 4 more Smart Citations
“…The broad DT distribution indicates the presence of multiple isomers of C 10 H 16 O 3 in the PSOA mixture. Previous study investigating isomers of C 10 H 16 O 3 generated in the ozonolysis of α-pinene reported the presence of up to three individual peaks for C 10 H 16 O 3 species ionized as Na + adducts . Therefore, the two small shoulder peaks on both the compact and extended sides of DT distribution may be related to isomers or conformers of pinonic acid + Na + , while the abundant peak centered at 21.66 ms most likely corresponds to pinonic acid.…”
Section: Resultsmentioning
confidence: 89%
“…Previous study investigating isomers of C 10 H 16 O 3 generated in the ozonolysis of α-pinene reported the presence of up to three individual peaks for C 10 H 16 O 3 species ionized as Na + adducts. 84 Therefore, the two small shoulder peaks on both the compact and extended sides of DT distribution may be related to isomers or conformers of pinonic acid + Na + , while the abundant peak centered at 21.66 ms most likely corresponds to pinonic acid. On the other hand, we observe two distinct features (19.5 and 20.3 ms) in the DT distributions of C 10 H 16 O 3 in PSOA (Figure 3d) in negative mode.…”
Section: ■ Results and Discussionmentioning
confidence: 97%
See 3 more Smart Citations